Hak Waris Anak yang Dilahirkan melalui Perjanjian Surogasi - Putu Nita Yulistian; I Nyoman Putu Budiartha; I Wayan Arthanaya (Fakultas Hukum, Universitas Warmadewa, 2021)
The development of technology in the medical world has led to surrogation methods as an alternative for married couples who cannot have children due to medical indications. Surrogation is an agreement between a woman and the husband and wife to become pregnant by donating the embryo of the husband and wife into the woman's womb and the child born is handed over to the husband and wife who make this agreement. This raises legal issues, namely how the existence of a surrogation agreement according to the health law and the Civil Code and how the inheritance rights of children born as a result of the surrogation agreement. This study uses normative research with a statutory and conceptual approach using primary, secondary and tertiary legal materials. The results of this study indicate that the existence of a surrogation agreement does not exist specifically, but based on the logic of argumentum a contrario, article 127 paragraph (1) letter a of the Health Law, article 40 paragraph (2) and article 43 paragraph (3) letter b Government regulations concerning reproductive health prohibits the practice of surrogation in Indonesia and the surrogation agreement is declared invalid according to article 1320 of the Civil Code because it does not meet the objective requirements. If the child is born, according to the Marriage Law, the child has the right to inherit to the surrogate woman's legal husband or to the surrogate woman and her family. However, if the child is adopted by the biological parent, the civil relationship between the child and the biological parent will be cut off and the right to inherit from the adoptive parent, in this case the biological parent of the child.